Evaluation of The Use of Antibiotic Drugs in Outstanding Patients with Diabetes Mellitus with Complications of Diabetic Ulcus in Clinic X Pontianak - Oni Astri Herdani; Nurmainah Nurmainah; Ressi Susanti (Jurusan Farmasi Universitas Negeri Gorontalo, 2023)
Diabetic ulcers are a complication of diabetes mellitus. Diabetic ulcers are caused by poor circulation associated with peripheral neuropathy and peripheral vascular disease that can lead to infection. To prevent or treat infections, proper treatment is needed, one of which is by using antibiotic therapy. Inappropriate use of antibiotics can lead to an increased risk of antibiotic resistance. This study aims to describe the pattern of antibiotic use in patients with type 2 diabetes mellitus with complications of diabetic ulcers and the rationale for their use. This study uses a descriptive observational method with a cross-sectional research design. Retrospective data collection using a purposive sampling method. The results showed that the characteristics of patients with type 2 diabetes mellitus with complications of diabetic ulcers by gender were most common in women (65%) compared to men (35%), and most occurred in the age range 55-64 years (44%) with the most severe level in grade III (86%). The pattern of antibiotic use used was antibiotics with single therapy (93%) compared to combination antibiotics (7%). The single most widely used antibiotic was cefixime (31%). Evaluation of the accuracy of the use of antibiotics is the right dose (93.45%) and the right time interval of administration (83.17%).